The development of stardom : celebrity, image and the media : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts (Media Studies and Communication) - Hillgrove, Richard John (Massey University, 1996)
The Development of Stardom: Celebrity, Image and the Media argues that the phenomenon of stardom has little to do with 'stars' and more to do with psychological processes of 'fans' that create 'artificial' relationships with them. The thesis examines how the fans' bond with a star evolves through a cycle. This can be traced through the foundational stages of 'early attachment', to a period in which the fan feels self actualised by establishing a 'healthy' relationship with the star, and on to a phase where the bond fades. Here, fans either reattach to a new star or react possessively, by trying to hold on to a star despite the continued erosion of their bond. The thesis suggests that the bond the fan forms with the star is false, and yet despite fans often being conscious of their 'fandom', true detachment from a reliance on stars is particularly difficult.
Keywords: Fans (Persons); Celebrities; Popular culture